2017
DOI: 10.1016/j.ebiom.2017.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Specific Sirt1 Activator-mediated Improvement in Glucose Homeostasis Requires Sirt1-Independent Activation of AMPK

Abstract: The specific Sirt1 activator SRT1720 increases mitochondrial function in skeletal muscle, presumably by activating Sirt1. However, Sirt1 gain of function does not increase mitochondrial function, which raises a question about the central role of Sirt1 in SRT1720 action. Moreover, it is believed that the metabolic effects of SRT1720 occur independently of AMP-activated protein kinase (AMPK), an important metabolic regulator that increases mitochondrial function. Here, we show that SRT1720 activates AMPK in a Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 74 publications
3
24
0
Order By: Relevance
“…The results showed that the expression of Sirt1 was significantly reduced at the protein and mRNA levels in the diabetic mice. A previous study showed that the loss of Sirt1 contributed to glucose metabolic abnormalities in diabetics (35). To examine the role of Sirt1 in the glucose metabolic activities observed in diabetic mice, SRT1720, an activator of Sirt1, was used to reactivate Sirt1 in the diabetic mice.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that the expression of Sirt1 was significantly reduced at the protein and mRNA levels in the diabetic mice. A previous study showed that the loss of Sirt1 contributed to glucose metabolic abnormalities in diabetics (35). To examine the role of Sirt1 in the glucose metabolic activities observed in diabetic mice, SRT1720, an activator of Sirt1, was used to reactivate Sirt1 in the diabetic mice.…”
Section: Resultsmentioning
confidence: 99%
“…Several Sirtuin isoforms appear to bear potential for being used as therapeutic targets, but to date only modulators of SIRT1 have entered into the clinic. The natural STAC resveratrol suffered from low bioavailability and potency, and - like early synthetic STACs such as SRT1720 – from limited target specificity (Pirola and Frojdo, 2008; Huber et al, 2010; Nguyen et al, 2013b; Park et al, 2017). This review will concentrate on a SIRT1 inhibitor and novel synthetic SIRT1 activators with superior properties that have advanced into the clinic.…”
Section: Sirtuin Modulators As Therapeutic Drugs – State Of the Artmentioning
confidence: 99%
“…Similarly, AMPK activator, R419, reportedly increased glucose uptake and GLUT4 promotor activity in C2C12 myotubes [57]. SRT170 provides another compound with which AMPK activation and mitochondrial biogenesis can be upregulated in C2C12 myotubes [92]. Peroxisome proliferator-activated receptor (PPAR) β/δ levels increase in skeletal muscle during exercise and are central to exercise-mediated metabolic regulation.…”
Section: Other Pharmacological Compoundsmentioning
confidence: 99%